First record of the genus Yalvaciana (Tettigoniidae; Tettigoniinae; Platycleidini) with the description of a new species from India - Shah, Muzamil Syed; Usmani, Mohd Kamil (Zootaxa, 2021)
The genus Yalvaciana Ciplak et.al (2002) is reported for the first time from India represented by a new species. Previously the genus comprised a single species, Yalvaciana yalvaci Demirsoy, (1974). Brief information about morphology, distribution and key to species are given. The Holotype has been deposited in the Museum of Zoology Department, AMU (ZDAMU).